Demographic and socio-economic risk factors associated with self-reported TB - Kapwata, T; Breetzke, G; Wright, C Y; Marcus, T S; Eales, O (The international journal of tuberculosis and lung disease, 2022)
The infectiousness of is known to be shaped by the human environment, with research showing positive associations with poverty, homelessness and overcrowding, among other factors. In this study, the focus is primarily on environmental health risks for TB, particularly on those associated with sociodemographic and household living conditions in South Africa. Data for this study were collected between 2014 and 2019 from a number of sites implementing community-oriented primary care (COPC) in the Gauteng Province of the country. Community health workers (CHWs) used AitaHealth , a custom-built mobile information management application, to obtain data on the TB status and environmental conditions of households. Statistical models were used to determine associations between various demographic, socio-economic and environmental risk factors, and TB. Approximately 12,503 TB cases were reported among 7,769 households. Substance use and male-headed households were found to have significant associations in households with at least one individual with TB. Overcrowding, as well as lack of access to piped water and adequate sanitation were also found to be positively associated with a 'TB-household.´ Improvements in housing and services, particularly the provision of piped water and reticulated flush toilets, are needed to control and prevent TB in South Africa.